Effect of green coffee on miR-133a, miR-155 and inflammatory biomarkers in obese individuals - Naglaa F. Khedr; Enas S. Zahran; Abla M. Ebeid; Samuel T. Melek; Rehab H. Werida (Diabetology & Metabolic Syndrome)
Abstract Objectives Metabolic syndrome is a cluster of conditions that increases the risk of atherosclerotic cardiovascular diseases. The current study was a randomized, double blind, placebo-controlled study that aimed to determine the impact of green coffee (GC) in obese patients with metabolic syndrome through analysis of miRNA-155, miRNA-133a and the inflammatory biomarkers such as resistin, TNF-α, total sialic acid, homocysteine, high sensitivity C-reactive protein (hs-CRP), and the anti-inflammatory cytokine, adiponectin. Methods One hundred-sixty obese patients were randomly supplemented either with GC capsules (800 mg) or placebo daily for six months. Both groups were advised to take a balanced diet. Blood samples were collected at baseline and after six months of supplementation. Results GC supplementation for 6 months reduced BMI (p = 0.002), waist circumference (p = 0.038), blood glucose (p = 0.002), HbA1c% (p = 0.000), Insulin (p = 0.000), systolic blood pressure (p = 0.005), diastolic BP (p = 0.001) compared with placebo. GC significantly decreased total cholesterol (TC, p = 0.000), LDL-C (p = 0.001), triglycerides (TG, p = 0.002) and increased HDL-C (p = 0.008) compared with placebo group. In addition, GC significantly (p ≤ 0.005) reduced total sialic acid, homocysteine, resistin, TNF-α, hs-CRP and the oxidative stress marker malondialdehyde (MDA), but increased serum adiponectin (p = 0.000) compared to placebo group. There was a significant reduction in the gene expression of miR-133a (p = 0.000) in GC group as compared with baseline levels and with the control placebo group (p = 0.001) after 6 months. Conclusion GC administration modulated metabolic syndrome by decreasing BMI, high BP, blood glucose, dyslipidemia, miRNA-133a and inflammatory biomarkers that constitute risk factors for cardiovascular diseases. ClinicalTrials.gov registration No. is NCT05688917. Graphical Abstract